Impedance Spectroscopy Investigation of ZnO Nanorod Doped Polymer-Dispersed Liquid Crystal for Ethanol Gas Sensing. (12th August 2020) - Liu, Yourong; Zheng, Jihong; Zhu, Qing; Shen, Tong; Chen, Qi
Abstract : This work reports an analysis of the impedance spectra obtained for a polymer-dispersed liquid crystal film doped with ZnO nanorods, during exposure to ethanol gas. ZnO nanorods doped composites were characterized by scanning electron micrography, Nyquist plots and an equivalent circuit model. The impedance values decreased greatly, and conductivity and relaxation frequency increased, when films came into contact with ethanol. The frequency response was highest (60) at 1 KHz. At the high frequency, the Nyquist plots revealed only one semicircle and the relaxation time varied from 4.5 × 10 −5 to 3.4 × 10 −7 s. Similar relaxation behavior at different temperatures was also noted. The conductivity values were two orders higher with ethanol gas and increased as the applied voltage increased. The capacitive value of the element in the equivalent circuit was related to the dipolar polarization and found not to be affected by the presence of the ethanol gas. The calculated significant differences among the constant phase element parameters provided a basis for a detection for ethanol gas. The results show that as a new type of stable structure and easily-made sensing film, this material has high sensitivity and good selectivity for ethanol molecules.